2018
DOI: 10.3389/fmicb.2018.00643
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and Culture Based Analysis of Chronic Rhinosinusitis Compared to Healthy Sinus Mucosa

Abstract: The role of bacteria in chronic rhinosinusitis (CRS) is still not well understood. Whole microbiome analysis adds new aspects to our current understanding that is mainly based on isolated bacteria. It is still unclear how the results of microbiome analysis and the classical culture based approaches interrelate. To address this, middle meatus swabs and tissue samples were obtained during sinus surgery in 5 patients with CRS with nasal polyps (CRSwNP), 5 patients with diffuse CRS without nasal polyps (CRSsNP), 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 45 publications
(64 reference statements)
4
31
0
3
Order By: Relevance
“…Data about lower number of Bifidobacterium in PS, ES and EC groups are in contrast with culture-based results. Other authors also reported that species, isolated from culture did not generally correspond with the most abundant genera in microbiome analysis (Koeller et al, 2018). For example, increased Bifidobacterium abundance was detectable only with an in vitro culture method, and not pyrosequencing (Finegold et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Data about lower number of Bifidobacterium in PS, ES and EC groups are in contrast with culture-based results. Other authors also reported that species, isolated from culture did not generally correspond with the most abundant genera in microbiome analysis (Koeller et al, 2018). For example, increased Bifidobacterium abundance was detectable only with an in vitro culture method, and not pyrosequencing (Finegold et al, 2014).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Chowdhury et al 34 demonstrated that CNNs can be leveraged for classification of (OMC) inflammation on CT. Their analysis was limited to evaluation of a single selected coronal image through the OMC and did not focus on the paranasal sinuses. Although previously considered a critical region of disease in CRS, its questionable degree of importance has been reconsidered in recent years 35‐37 . We are not aware of other studies in which CNNs have been used to automate calculation of sinus opacification.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examining the nasal microbiome resulted in inconsistent outcomes for alpha diversity indices in CRS patients compared to those in the control group. Some studies reported that there was no significant difference in alpha diversity between the control and the CRS patients(Koeller et al 2018; Mahdavinia et al 2018; Paramasivan et al 2019). Meanwhile, other studies reported that the alpha diversity indices significantly decreased in CRS patients compared to those in the control group(Choi et al 2014; Biswas et al 2015; Cope et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For the medical treatment of CRS, antibiotics such as penicillins/betalactams and macrolides were prescribed in about 70% of CRS visits(Smith et al 2013). However, most of previous metagenomic analyses(Aurora et al 2013; Choi et al 2014; Biswas et al 2015; Ramakrishnan et al 2015; Biswas et al 2017; Cope et al 2017; Hoggard et al 2017; Jain et al 2017; Lal et al 2017; Ramakrishnan et al 2017; Chalermwatanachai et al 2018; Copeland et al 2018; Koeller et al 2018; Mahdavinia et al 2018; Biswas et al 2019; Gan et al 2019; Paramasivan et al 2019; Rom et al 2019) examining CRS excluded patients who had taken antibiotics within approximately one month prior to sampling. Here, we performed metagenomics and proteomics analyses using nasal secretions in healthy control and CRS patients.…”
Section: Introductionmentioning
confidence: 99%